The Influence of Career Development, Supervision, and Employee Commitment on Employee Performance at the Lubuk Pakam Pratama Tax Service Office - Yusuf, Faisal; Sartika, Hikmah; Hutagalung, Lukman Hakim; Sahaimi, Sahaimi; Wasesa, Supar; Sadly, Efendi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This survey means to pick the impact of transporter improvement, oversight and commitment delegate fairly and in the mean time on the introduction of representatives work in the Kantor Pelayanan Pajak Pratama Lubuk Pakam with an overall public of 122 individuals and a study test. of 55 individuals. The information evaluation system utilized is different apostatize assessment utilizing the IMB Encounters PC program for Thing and Association Game-Plan (SPSS) change 24. Taking into account the appraisal results, transporter improvement basically impacts the presentation of the specialists work of the Kantor Pelayanan Pajak Pratama Lubuk Pakam. This is kept up with by the possible results of t-count evaluation > t-table (2,063 > 2,008) at n = 55 at 95% importance level.